2007
DOI: 10.1007/s11270-007-9361-9
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Quotients for Ammonia Volatilization from Four Soils in Potato Production Regions

Abstract: Ammonia (NH 3 ) emission from nitrogen (N) fertilizers used in agriculture decreases N uptake by the crop and negatively impacts air quality. In order to better understand the factors influencing NH 3 emission from agriculture, this research was conducted with four major soils used for potato production: Biscayne Marl Soil (BMS, pH 7.27), and Krome Gravelly Loam (KGL, pH 7.69) from Florida; and Quincy Fine Sand (QFS, pH 6.65), and Warden Silt Loam (WSL, pH 6.46) from Washington. Potassium nitrate (KNO 3 ), amm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 32 publications
(41 reference statements)
2
18
0
Order By: Relevance
“…The results for all four soil types showed that the lower the soil moisture content, the higher the amount of NH 3 volatilization (Liu et al, 2007). Water acts a solvent to transport NH 4 + away from the soil surface (Liu et al, 2007). The drier bedded pack during the hot months may have contributed to higher concentration of NH 3 in the air samples from the pen surface of BDMF.…”
Section: Effect Of Bedded Pack Characteristics On Ammonia Concentratimentioning
confidence: 97%
See 4 more Smart Citations
“…The results for all four soil types showed that the lower the soil moisture content, the higher the amount of NH 3 volatilization (Liu et al, 2007). Water acts a solvent to transport NH 4 + away from the soil surface (Liu et al, 2007). The drier bedded pack during the hot months may have contributed to higher concentration of NH 3 in the air samples from the pen surface of BDMF.…”
Section: Effect Of Bedded Pack Characteristics On Ammonia Concentratimentioning
confidence: 97%
“…Jeppsson (1999) reported an increase in NH 3 emissions in deep-bedded dairy barns when the temperature of the bedded pack increased from 21.4°C to 30.0°C. Elevating the temperature of the soil has been shown to increase NH 3 losses from the surface of open feedlots (Sherwood et al, 2006) and from soils receiving urea fertilizer (Liu et al, 2007). Higher temperatures also increased NH 3 losses from waste treatment lagoons (Aneja et al, 2001) and poultry litter (Liu et al, 2006).…”
Section: Effect Of Bedded Pack Characteristics On Ammonia Concentratimentioning
confidence: 99%
See 3 more Smart Citations